Lumen‐apposing metal stents for drainage of pancreatic fluid collections: When and for whom?. Issue 1 (15th June 2016) - Bang, Ji Young; Hasan, Muhammad K.; Navaneethan, Udayakumar; Sutton, Bryce; Frandah, Wesam; Siddique, Sameer; Hawes, Robert H.; Varadarajulu, Shyam
Abstract : Background and Aim: Although lumen‐apposing metal stents (LAMS) are increasingly being used for drainage of pancreatic fluid collections (PFC), their advantage over plastic stents is unclear. Methods: In this retrospective case–control study, 20 patients who underwent PFC drainage using LAMS were matched with 40 patients treated with plastic stents according to PFC type (walled‐off necrosis [WON] vs pseudocyst) and procedural technique (conventional vs multi‐gate). Main outcome measures were treatment success, reintervention, clinical and stent‐related adverse events, procedural duration, length of hospital stay (LOS) and hospital costs. Results: At median follow up of 570 days, except for median procedural duration (8.5 vs 25 min, P  < 0.001), there was no significant difference in treatment success (95.0 vs 92.5%, P  = 0.99), reintervention (25.0 vs 30.0 %, P  = 0.77), clinical (10.0 vs 12.5 %, P  = 0.99) and stent‐related adverse events (10.0 vs 2.5 %, P  = 0.26) or median LOS (2 [IQR 1–5] vs 2 [IQR 1–7] days, P  = 0.58) between patients treated with LAMS versus plastic stents. Although there was no difference for WON ($16 708 for LAMS vs $17 221 for plastic stents, P  = 0.90), mean hospital costs were significantly lower for pseudocysts using plastic stents ($18 996 vs $58 649, P  = 0.03). Conclusions: Although there is no difference in clinical outcomes, treating pseudocysts using plastic stents is less expensive. It is also possible that the short procedural duration is a surrogate marker for procedural complexity and this may drive the use of LAMS in sicker patients.